PENGARUH JENlS PELARUT ORGANIK DAN UMUR DAUN PINUS TERHADAP RENDEMEN LILIN - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1995)
The  objective    of  this  research   is  to  study    the  effect  of  organic   solvents    and  pine   needles age  on  wax   yields.   The  organic   solvents   used  in  extracting  wax consisted  of  chloroform,    n hexane  and   ethanol; however,  the  radiate  pine   needles'     age   used   as  raw   materials  for  the   action were  primary   pine   needles  (one  year   old  or  less),   secondary   pine   needles   (two   o tu,   e years   old),  and  mixtare  of  both.  the  data   were  analysed  with  an A  x  B factorial  design  where   A   represented   organic  solvents    and   B  depicted   pine  needles'   age.    the   differenc  between   means  of wax   yields   was  calculated   with  an  LSD   method   in  the    SAS   compute packages.Results   showed   that  organic   solvents,   pine   needles'   age  and  the  interaction   of both   gave  ,high fr  significance  on  wax  yields.    Compared    lo  the   other   combinations,    a  combination    of. chtorofonn    solvent   and  secondary    pine   needles   produced   the  highest   of  wax  yield.   A  wax yiet. obtained   by  extracting   secondary   pine   needles   was  statistically     similar lo   a wax yield  obtaine, frotn  a mixture   of  both   primary    and  secondary    pine   needles.    A  chloroform  solvent   is  a  goo. solvent   to  extract   pine  needle   waxes  from  any  kind  of pine   species.